Selective changes of ocular vestibular myogenic potentials in Parkinson's disease. Issue 4 (27th December 2014) - Pötter‐Nerger, Monika; Govender, Sendhil; Deuschl, Günther; Volkmann, Jens; Colebatch, J.G.
ABSTRACT Background Vestibular evoked myogenic potentials represent electrophysiological tools to measure vestibular reflex actions at different levels of the brainstem in Parkinson's disease. Objective To investigate cervical and ocular vestibular myogenic potentials in Parkinsonian patients with mild disability. Methods In 13 Parkinsonian patients and 13 age‐matched healthy controls, cervical and ocular vestibular myogenic potentials were recorded after unilateral air‐conducted tone bursts and bone‐conducted stimuli delivered at the forehead or mastoids. Results In contrast to relatively preserved cervical vestibular evoked myogenic potentials, ocular vestibular evoked myogenic potentials were significantly delayed and of reduced amplitude, particularly after impulsive stimulation in Parkinsonian patients. Levodopa had no significant effect on either type of response. Conclusion In mild to moderate Parkinson's disease, altered ocular vestibular myogenic potentials may indicate early functional involvement of the upper brainstem, in contrast to preserved lower brainstem function as reflected by normal cervical vestibular myogenic potentials. © 2014 International Parkinson and Movement Disorder Society